2019
DOI: 10.1017/pab.2019.31
|View full text |Cite
|
Sign up to set email alerts
|

Bony lesions in early tetrapods and the evolution of mineralized tissue repair

Abstract: Bone healing is an important survival mechanism, allowing vertebrates to recover from injury and disease. Here we describe newly recognized paleopathologies in the hindlimbs of the early tetrapods Crassigyrinus scoticus and Eoherpeton watsoni from the early Carboniferous of Cowdenbeath, Scotland. These pathologies are among the oldest known instances of bone healing in tetrapod limb bones in the fossil record (about 325 Ma). X-ray microtomographic imaging of the internal bone structure of these lesions shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 129 publications
(226 reference statements)
1
10
0
Order By: Relevance
“…Histological studies from the intervening Carboniferous Period are largely lacking, due to the rarity of tetrapod fossils preserved in Mississippian rock (Anderson et al, 2015; Clack, 2002; Coates & Clack, 1995; Otoo et al, 2019; Romer, 1956; Warren & Turner, 2004). Other than two studies examining pathological bone (Bishop et al, 2015; Herbst et al, 2019) and vertebral elements in a few Carboniferous taxa (Danto et al, 2016, 2017), there is a scarcity of osteohistological data for nearly 60 million years of tetrapod evolution (Figure 1). However, it is during this time period that the critical transition from fully aquatic to fully terrestrial tetrapods is inferred to have taken place (Dickson et al, 2021; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Histological studies from the intervening Carboniferous Period are largely lacking, due to the rarity of tetrapod fossils preserved in Mississippian rock (Anderson et al, 2015; Clack, 2002; Coates & Clack, 1995; Otoo et al, 2019; Romer, 1956; Warren & Turner, 2004). Other than two studies examining pathological bone (Bishop et al, 2015; Herbst et al, 2019) and vertebral elements in a few Carboniferous taxa (Danto et al, 2016, 2017), there is a scarcity of osteohistological data for nearly 60 million years of tetrapod evolution (Figure 1). However, it is during this time period that the critical transition from fully aquatic to fully terrestrial tetrapods is inferred to have taken place (Dickson et al, 2021; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Bone repair without resorption .U values tend towards 0 as the overlap between the two groups' rank distributions decreases to 0. All groups have n = 6 except rested tibia and rested metacarpal diaphysis which have n may occur by organic and inorganic substrates bridging and sealing cracks [30,47], which might be an inherent property of mineralised tissues occurring across all vertebrate taxa like bone remodelling is [48]. In vitro mechanical testing of bone specimens machined from the third metacarpal of Thoroughbred racehorses showed that the elastic modulus and yield strength of specimens were not significantly affected by prior fatigue loading equivalent to a lifetime of racing [49].…”
Section: Discussionmentioning
confidence: 99%
“…This represents growing circumvascular bone. Thus, a developmental series can be proposed following damage: (1) an initial (hypothetical) inflammatory phase and formation of a haematoma (Maruyama et al, 2020, although not as large a response as in mammal repair [Moss, 1962; Herbst et al, 2019]); (2) blood vessels enter the area, with osteoclasts resorbing original bone to prepare a margin for new bone deposition (vascular response being crucial in mammalian bone healing; Tomlinson & Silva, 2013); (3) osteoblasts at this resting surface deposit woven bone that entraps the anchoring fibres, normal to these intrinsic fibres, and thicker; (4) woven bone surrounds vascular canals; (5) the size of the vascular canal decreases with layers of organised bone surrounding the canal space, representing the circumvascular bone; (6) all woven bone is eventually resorbed and only organised, fine fibered bone remains.…”
Section: Discussionmentioning
confidence: 99%